2022
DOI: 10.1038/s41598-022-15360-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of endogenously produced hydrogen sulfide (H2S) and persulfidation in male reproduction

Abstract: Persulfidation contributes to a group of redox post-translational modifications (PTMs), which arise exclusively on the sulfhydryl group of cysteine as a result of hydrogen sulfide (H2S) action. Redox-active molecules, including H2S, contribute to sperm development; therefore, redox PTMs represent an extremely important signalling pathway in sperm life. In this path, persulfidation prevents protein damage caused by irreversible cysteine hyperoxidation and thus maintains this signalling pathway. In our study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…4 . Green fluorescence was observed in sperm cells from all treatments, including the Ctr group, which confirms the endogenous H 2 S production in porcine spermatozoa [ 20 ]. Fluorescence intensity could not be determined because of fast quenching.…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…4 . Green fluorescence was observed in sperm cells from all treatments, including the Ctr group, which confirms the endogenous H 2 S production in porcine spermatozoa [ 20 ]. Fluorescence intensity could not be determined because of fast quenching.…”
Section: Methodsmentioning
confidence: 71%
“…This study aimed to investigate the effect of NTAs on sperm function under different in vitro conditions: during short-term incubation and under induced oxidative stress. For these experiments, porcine spermatozoa were used as a cell model because of the known role of H 2 S in the sperm biology of this species [ 6 , 7 , 19 , 20 ]. Because carbonic anhydrase function is essential for H 2 S release from NTAs, we first quantified the activity of this enzyme in each ejaculate component: sperm cells and seminal plasma.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S generation systems have been found in the mammal reproductive systems [14][15][16]. With regard to its role in the male reproductive system, H 2 S promotes the relaxation of human cavernous smooth muscle, mediates erectile function [17][18][19][20], enhances spermatogonial proliferation [21,22], and regulates the relaxation of vas deferens smooth muscle [23,24]. Among the effects of H 2 S on the female reproductive system, H 2 S suppresses the natural contraction of uterine bands taken from pregnant rats [25], notably relaxes vaginal smooth muscle in rabbits [16], modulates oviductal transport [26], and causes placental metamorphosis [27].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that one-carbon metabolism dysfunction, particularly the dysfunction of the transsulfuration enzymes CBS and CSE, plays a role in male infertility 20,21 , and also a speci c de cit in the H 2 S output is reported 19 . In the sperm, the persul dation of proteins, including glyceraldehyde-3phosphate dehydrogenase (GAPDH), tubulin, and anchor protein A-kinase, as a part of the redox signaling pathway, is strongly controlled via enzymatic H 2 S formation and is needed for sperm viability 22 .…”
Section: Introductionmentioning
confidence: 99%